Thermomagnetic ferroconvection in an anisotropic permeable layer exposed to a modulated magnetic field (International Journal of Mathematics and Physics, 2023)
The impact of a sinusoidal mode of magnetic field involving time-dependent on the threshold of magnetic smart liquid advection in a saturated Darcy-permeable framework is investigated using a regular perturbation technique. Anisotropic permeability and thermal anisotropy are used to describe the flow through permeable medium. The regular perturbation technique is based on minimum amplitude of time-fluctuated magnetic field, the threshold condition is computed with regard to correction in a critical Rayleigh number and wavenumber. Correction in Rayleigh number is identified by modulating the magnetic field, modulation frequency, magnetic parameter, mechanical anisotropy, thermal anisotropy and Vadasz number. At intermediate frequency values, the impact of various physical factors is perceived to be noteworthy. It is found that by fine tuning the frequency of magnetic field modulation, we can either accelerate or postpone the onset of ferroconvection. The most sophisticated scientific application packages, Wolfram Mathematica 11.3 is used to extract the numerical values as well as plotting graphs. The problem sheds some light on convective heat transfer mechanisms in ferromagnetic fluid with time-varying magnetic field.